Efficacies of new age fungicides against charcoal rot of sesame: Efficacies of new age fungicides against charcoal rot of sesame - SHIVANI NAGPURE; K N GUPTA; AKSHAY SALBARDE (Journal of Oilseeds Research, 2023)
Six systemic fungicides were evaluated under in vitro condition by using poison food techniques at three different concentrations 500 ppm, 1000 ppm and 1500 ppm against root and stem rot pathogen of sesame (Macrophomina phaseolina) Tassi Goid. all the treatments were found to be superior over control in which T1 (Tebuconazole 50% + Trifloxystrobin 25%), gave 100% inhibition against test fungus (M. phaseolina) at all the concentrations (500, 1000 and 1500 ppm) followed by T6 (Carbendazim + Mencozeb), which gave 94.43% of average inhibition, followed by T5 (Captan + Hexaconazole), that gave 92.59% of average inhibition, followed by T4 (Cymoxanil + mencozeb) gave 83.15% average inhibition, followed by T5 (Pyraclostrobin + Metiram) with 57.28% of average inhibition. Least mycelial inhibition was given by T2 (Azoxystrobin) with only 41.66%.